Preserving the free education movement in UP Diliman through archival activism - Dela Cruz, Daniel Paulo F. (School of Library and Information Studies, University of the Philippines Diliman, 2018)
After decades of struggle to fight for free education in the university, the student movement finally reached a major milestone of success in the enactment of the Universal Access to Quality Tertiary Education Act. However, looking into the history of the free education movement in the Philippines, it has been realized that there are limited narratives that account for its beginnings and developments. This study explores the role of archival activism in supporting the student movement situated in UP Diliman through an institution-community collaboration. Further, this study emphasized the role of archival practice in providing social power, pursuing social justice, and supporting social memory for these activist groups.